Mechanisms of change of a multifaceted implementation strategy on fidelity to a guideline for the prevention of mental health problems at the workplace: a mechanism analysis within a cluster-randomized controlled trial - Andreas Rödlund; Anna Toropova; Rebecca Lengnick-Hall; Byron J. Powell; Liselotte Schäfer Elinder; Christina Björklund; Lydia Kwak (Implementation Science)
Abstract Background Occupational guidelines exist to support workplaces with the prevention of mental health problems (MHP) among their staff. However, knowledge of effective implementation strategies to support their implementation is limited. This study experimentally tested whether a multifaceted implementation strategy – comprising an educational meeting, five workshops, implementation teams, small cyclical tests of change, and facilitation – improves fidelity to a guideline for preventing MHP in a school setting through the pathway of change of the Capability Opportunity Motivation-Behavior (COM-B)-model. To gain a more granular understanding of the mechanisms of change, the Theoretical Domains Framework (TDF) was used to specify mediators related to capability, opportunity, and motivation. This study tested whether the multifaceted strategy versus a discrete strategy (1) improves fidelity, (2) enhances capability, opportunity, and motivation over time, and (3) if the strategy’s effect on fidelity is mediated by capability, opportunity, and motivation. Methods Fifty-five schools were randomly assigned to a multifaceted strategy or a discrete strategy. Fidelity was measured by questionnaires at baseline and 12 months, while capability, opportunity, and motivation were assessed three times within this period (directly after the educational meeting and at three and nine months). The Determinants of Implementation Behavior Questionnaire was used to assess TDF hypothesized mediators corresponding to the COM-B components. Separate pathways were analyzed for each mediator. Linear Mixed Modeling was employed to test the strategy’s effect on fidelity, and mediation analyses were conducted using the PROCESS Macro. Results The multifaceted strategy led to improved fidelity at 12 months (B = 2.81, p < .001). Multifaceted schools reported higher scores for all mediators after nine months compared to schools receiving the discrete strategy. The effect of the multifaceted strategy on fidelity was partially mediated by all TDF mediators (p =  < .05) except for beliefs about consequences. Capability-related mediators, including skills (Proportion-mediated = 41%, p =  < .01) and behavioral regulation (Proportion-mediated = 35%, p =  < .001), accounted for the largest proportion of the effect, followed by the motivation-related mediator goals (Proportion-mediated = 34%, p =  < .01). Conclusions The multifaceted strategy improved guideline fidelity by enhancing capability, opportunity, and motivation confirming the proposed function of COM-B. This study addresses calls for experimental evidence on how multifaceted implementation strategies achieve implementation outcomes. Trial registration ClinicalTrials.org dr.nr 2020–01214.